New tribe Labiobaetini tribus n., redefinition of Pseudopannota Waltz & McCafferty 1987 and descriptions of new and little known species from Zambia and Uganda - Kluge, Nikita J.; Novikova, Eugenia A. (Zootaxa, 2016)
A new tribe Labiobaetini tribus n. is established for a plesiomorphon Labiobaetis Novikova & Kluge 1987 and a holophyletic taxon Pseudopannota Waltz & McCafferty 1987. New synonymy Pseudopannota Waltz & McCafferty 1987 = Ophelmatostoma Waltz & McCafferty 1987, syn. n. is proposed. A new species Pseudopannota pannota sp. n. closely related to P. berthrandi (Demoulin 1967) is described from Zambia based on imagoes of both sexes reared from larvae. Pseudopannota camerunense (Ulmer 1920) comb. n. is redescribed from Zambia based on imagoes of both sexes reared from larvae. A new species Pseudopannota fusca sp. n. is described from Uganda based on larvae and subimagoes of both sexes extracted from mature larvae. Pseudopannota maculosa (Crass 1947) is reported from Zambia based on larvae. Labiobaetis tenuicrinitus (Kopelke 1980) comb. n. (= Baetis spatulatus Gillies 1994 syn. n.) is redescribed from Uganda based on imagoes of both sexes reared from larvae.